Implementing capnography for lactate-enhanced qSOFA scores: Sepsis diagnosis in EMS settings - Li, Donny; Sun, Jeffrey; Zhao, Lucy (The Meducator, 2022)
Sepsis is a life-threatening condition that occurs when the body produces a pro-inflammatory immune response to infection, leading to a decrease in blood flow that results in organ failure and death. Sepsis has the ability to kill within hours, and is responsible for 20% of deaths globally. However, current diagnostic techniques in the pre-hospital setting are limited by time and resources. It has recently been found that sepsis screening tools like qSOFA and lactate biomarkers used within the hospital could supplement diagnostic needs within the EMS setting. With research showing that lactate levels can be indirectly and instantaneously measured via capnography by EMS personnel, this technique may complement existing sepsis screening tools to achieve faster diagnosis. This article investigates the current flaws of sepsis diagnosis within the EMS setting and evaluates the benefits of the implementation of qSOFA and lactate technology.